Octahedral spinel electrocatalysts for alkaline fuel cells - Yang, Yao (Proc Natl Acad Sci U S A, 2019)
Designing high-performance nonprecious electrocatalysts to replace Pt for the oxygen reduction reaction (ORR) has been a key challenge for advancing fuel cell technologies. Here, we report a systematic study of 15 different AB(2)O(4)/C spinel nanoparticles with well-controlled octahedral morphology. The 3 most active ORR electrocatalysts were MnCo(2)O(4)/C, CoMn(2)O(4)/C, and CoFe(2)O(4)/C. CoMn(2)O(4)/C exhibited a half-wave potential of 0.89 V in 1 M KOH, equal to the benchmark activity of Pt/C, which was ascribed to charge transfer between Co and Mn, as evidenced by X-ray absorption spectroscopy. Scanning transmission electron microscopy (STEM) provided atomic-scale, spatially resolved images, and high-energy-resolution electron-loss near-edge structure (ELNES) enabled fingerprinting the local chemical environment around the active sites. The most active MnCo(2)O(4)/C was shown to have a unique Co-Mn core–shell structure. ELNES spectra indicate that the Co in the core is predominantly Co(2.7+) while in the shell, it is mainly Co(2+). Broader Mn ELNES spectra indicate less-ordered nearest oxygen neighbors. Co in the shell occupies mainly tetrahedral sites, which are likely candidates as the active sites for the ORR. Such microscopic-level investigation probes the heterogeneous electronic structure at the single-nanoparticle level, and may provide a more rational basis for the design of electrocatalysts for alkaline fuel cells.